Revisioning Financial Education: Shortcomings and Opportunities for Transformation - Paul, Lara; Knudson, Sarah (Journal of the Canadian Association for Curriculum Studies, 2023)
Early, comprehensive and contextually relevant instruction in financial literacy for youth has been found to positively influence financial behaviours as well as psychosocial outcomes such as stress management and feelings of self-efficacy. Yet, financial literacy resources and secondary school curricula have several key limitations, such as piecemeal delivery, which hinder their potential to promote positive and lasting habits. With a focus on the Canadian context, we first assess the potential benefits and limitations of financial literacy education. We then present and assess a newly released financial education curriculum package from Western Canada, analyzing its proposed delivery framework and possibilities for implementation elsewhere.